On Potamocypris compressa (Crustacea, Ostracoda) from temporary rock pools in Utah, USA, with notes on the taxonomic harmonisation of North American and European ostracod faunas - Horne, David J.; Jocque, Merlijn; Brendonck, Luc; Martens, Koen (Zootaxa, 2011)
We report the abundant occurrence of a species of the ostracod genus Potamocypris in temporary freshwater rock pools in Utah, USA. It is identified as P. compressa Furtos, 1933, a species hitherto considered to be only a variety or subspecies of P. smaragdina (Vávra, 1891) but here established as a valid species for the first time. The biogeographical implications of this taxonomic revision are considered in the context of a metadatabase of northern hemisphere nonmarine ostracods for palaeoclimate applications.